The young Rafael Gutiérrez Girardot. Notes for an intellectual biography: the discovering of Jorge Luis Borges and his stimulating influence (2009)
The article attempts to bring to light the intellectual stimulus felt by the essayist Rafael Gutiérrez Girardot through his discovery of Jorge Luis Borges literature. To guide us in demonstrating this intellectual stimulation we will use some of Girardot‘